Knowledge integration improves flood disaster management: a case study of Kemaman - Zakaria, Nor Hidayati; Ahmad, Mohammad Nazir; Mohd Noor, Mohd Saiful Anuar; Ahmad, Mazida (2016)
This paper discusses the flood knowledge integration practices that have been applied in the flood management team of Kemaman District, Terengganu, Malaysia. The Kemaman District was announced to be the first district who had achieved a Gold Standard for flood disaster management practices. Accordingly, this study applies a case study approach by means of: interviewing key informants; studying archival documents; and conducting site visits to flood locations so as to better understand the achievement of the district’s flood management team. The result shows the importance of knowledge integration as one of the factors contributing to the success of the district’s flood management plan.